Analysing the Impact of Fruit Bats (Rousettus leschenaulti and Cynopterus sphinx) in the Tropical Ecosystem of Tirunelveli District, Tamil Nadu, India - M. Stephen; C. Albert; G. Petchiammal; Juliet Vanitharani (Cutting Edge Research in Biology Vol. 1, 2022)
Fruit bat diversity in the Tirunelveli District ecosystem is important for pollinating flowers and seed dispersal. Two common megachiropterans or yinpterochiropterans Rousettus leschnaulti (fulvous fruit bat) and Cynopterus sphinx (greater short-nosed fruit bat) interacting in different agro and tropical forest ecosystem of Tirunelveli district has been selected as study animals for this impact analysis. A glimpse of the fruit bat’s bio-agent function in the ecosystem has been made possible by a variety of food choices, processing techniques, and the economic and ecological significance of plants dependent on bats. The evidence for the interaction of fruit bats and plants comes from the identification of stragglers from feeding roosts, observations with video recording, and mist-netting in the foraging locations. Their species-specific food preferences significantly contribute to the preservation of the social structures and long-term survival of particular taxa in the ecosystem. Despite playing a unique role, they have received little acknowledgment under Indian governmentlegislations and policies. The main objective of this paper examines and provides information about R. leschnaulti and C. sphinx selection of food and the patterns of resource usage which enable them play a major role in the seed dispersal of economically important plant species in the forest ecosystem and some of the beneficiaries are endemic and endangered.